Conceptual design of a hybrid thermal and photovoltaic receiver of an FMDF collector - Sulaiman, Mohd Yusof; Win, Maw Hlaing Oo; Abdul Wahab, Mahdi; Sulaiman, Zainal Abidin; Khouzam, Kame Y. (Elsevier Science, 1997)
The optical characteristic of a Fixed Mirror Distributed Focus (FMDF) solar collector is used as a basis for the design of an hybrid thermal and photovoltaic (PV) receiver. The result provides another variation in energy conversion that an FMDF solar collector can conveniently perform.